2009
DOI: 10.1016/j.ccr.2009.09.036
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic Stem Cell Expansion Precedes the Generation of Committed Myeloid Leukemia-Initiating Cells in C/EBPα Mutant AML

Abstract: We here use knockin mutagenesis in the mouse to model the spectrum of acquired CEBPA mutations in human acute myeloid leukemia. We find that C-terminal C/EBPalpha mutations increase the proliferation of long-term hematopoietic stem cells (LT-HSCs) in a cell-intrinsic manner and override normal HSC homeostasis, leading to expansion of premalignant HSCs. However, such mutations impair myeloid programming of HSCs and block myeloid lineage commitment when homozygous. In contrast, N-terminal C/EBPalpha mutations ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
168
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 132 publications
(179 citation statements)
references
References 36 publications
7
168
1
Order By: Relevance
“…Patients with K313dup had TCR rearrangements and CD7 expression (27), lymphoid features associated with unfavourable outcome and which we have previously linked with TRIB2 and C/EBPα perturbation (31). Previous investigation of the combination of a C-terminal mutation (K313 duplication) with C/EBPα p30 expression revealed co-operation and provides a possible explanation for the high prevalence of one N-term mutation and one C-term mutation in ~90% of biallelic C/EBPα mutant AMLs (23). We propose that the K313dup mutation in patients contributes to leukaemic transformation by increasing the susceptibility of C/EBPα to ubiquitination resulting in increased degradation of C/EBPα p42.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Patients with K313dup had TCR rearrangements and CD7 expression (27), lymphoid features associated with unfavourable outcome and which we have previously linked with TRIB2 and C/EBPα perturbation (31). Previous investigation of the combination of a C-terminal mutation (K313 duplication) with C/EBPα p30 expression revealed co-operation and provides a possible explanation for the high prevalence of one N-term mutation and one C-term mutation in ~90% of biallelic C/EBPα mutant AMLs (23). We propose that the K313dup mutation in patients contributes to leukaemic transformation by increasing the susceptibility of C/EBPα to ubiquitination resulting in increased degradation of C/EBPα p42.…”
Section: Discussionmentioning
confidence: 63%
“…This lysine residue is a common mutation in AML patients (~10% of all C/EBPα mutations) which results in the duplication of the single lysine to KK leading to reduced protein stability (27). Using mouse genetics it was shown that this duplication of K313 to K313KK (K313dup) resulted in an increased proliferation of long-term HSCs (LT-HSCs) leading to an expansion of premaligant HSCs not seen with the N-terminal mutations (23). Our data show that the absence of this lysine by mutation to an arginine (K313R) abrogates the susceptibility of C/EBPα to degradation whilst retaining its DNA binding and transcriptional activation function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 The combination of N-and C-terminal C/EBPa mutations incorporates premalignant HSC expansion and sufficient myeloid programming to allow the formation of common myeloid progenitor-derived LICs. 11 Although mice with biallelic Cebpa mutations eventually develop AML, additional genetic changes are required for leukemogenesis as indicated by the long latency period.…”
Section: Introductionmentioning
confidence: 99%
“…One strain contains an ITD mutation in the endogenous murine Flt3 locus, 14 which was cross-bred with a knockin of an N-terminal Cebpa mutation (Lp30 or L allele) 18 and a C-terminal Cebpa mutation (K313 duplication: K313KK or K allele). 11 This model for human AML enabled us to appropriately study the molecular and cellular background of leukemia initiation and maintenance. Expressed from its original promoter, the respective leukemogenic mutations acted at the correct developmental stage and physiological levels.…”
Section: Introductionmentioning
confidence: 99%